Transmission of the Global Bank Liquidity Shock: Evidence from the US Foreign Bank Loans to Southeast Asian Economies - Agus Salim; Ignatius Abasimi; Dini Yuniarti; Mahrus Lutfi Adi Kurniawan; Suripto Suripto; Naveed Aslam; Sunil Kumar Chaudhary (Journal of Economics Research and Social Sciences, 2023)
The empirical debate of foreign bank loans as an international intermediation transfer from industrialized to developing market economies, which concentrated on expenses and advantages, has continued. Our manuscript analyzes the determinants of US bank loans in selected Southeast Asian emerging markets. The most critical variables, based on the statistical approach built around the system-GMM, have a considerable effect on the growth rates of the origin and destination countries. Remarkably, the exchange rate significantly becomes a risk indicator which decrease the US bank flow. Finally, shock in the US economy has been transmitted to the Southeast Asian economies through foreign bank flow.